Relationship Marketing in Professional Services: A Case Study of Architectural Practice - Kilpady, Nikhil (2005)
Relationship Marketing has stimulated considerable interest as a new marketing paradigm in both the business and the academic worlds. This thesis contributes to the discussion by providing an analysis of the relationship formation process in professional services' with particular reference to architectural practice. It involves theoretical discussion of the content and context of professional service relationships, and a substantial case evidence of relationship initiation pertaining to an architecture firm in the UK, i.e. Lewis & Hickey Ltd. and their clients.